Fenomena Bahasa Gaul dan Eksistensi Bahasa Indonesia di Tengah Arus Globalisasi - Siti Nur Afifatul Hikmah (Jurnal Multidisiplin Ibrahimy)
The phenomenon of slang is a social reality in the era of globalization. Language has meaning in every statement or self-portrait. This research aims to study the validity of slang and its existence in the era of globalization. This study uses a qualitative method using a type of phenomenology. The data used are texts/documents, dialogues and other everyday phenomena and their existence. Data collection techniques were carried out by examining several natural phenomena related to adolescent slang. The material is then analyzed using Miles and Huberman Flow with the stages of data collection, data reduction, data presentation and verification. The results of this research show the impact of the slang phenomenon, namely (a) the existence of the Indonesian language is threatened by the marginalization of slang, (b) the collapse of Indonesian language standards, (c) the extinction of the Indonesian language, and d) distrust at the hands of Indonesians. Factors related to the slang phenomenon are (a) the spread of the internet and social networks, (b) environmental impacts, (c) the role of the media, and (d) developments over time.